دور استخدام المرأة الجزائرية الماكثة بالمنزل للإعلان التلفزي من أجل تحقيق اشباعاتها اليومية -استطلاع الكتروني موجه على عينة من النساء بولاية قسنطينة من مستخدمات موقع التواصل الاجتماعي فايسبوك- - طلحي, حمزة; ميلود, مراد (جامعة الوادي - University of Eloued, 2021)
سوف نستعرض من خلال هذا العمل العلمي مختلف النتائج العلمية المتوصل إليها من خلال دراسة استطلاع الكتروني عبر موقع التواصل الاجتماعي فايسبوك قمنا بها كفريق بحث علمي و التي استهدفت بطبيعة الحال محاولة معرفة كيفية استقبال ومشاهدة المرأة الماكثة بالمنزل بولاية قسنطينة للإعلان التلفزي. و من جملة ما تم التوصل إليه من نتائج مختلف التأثيرات التي يتركها هذا النوع من الإعلان على القيم و السلوكات وترسيخه للنمط الاستهلاكي الذي يخدم مصلحة المعلنين وليس مصلحة الجمهور خاصة إذا كان هذا الجمهور جمهور النساء الماكثات بالمنزل واللواتي لديهن بطبيعة الحال متسع من الوقت و متفرّغات تماما لمشاهدة مختلف الإعلانات التلفزيونية. Abstract: We will review, through this scientific work, the various scientific results reached through the study of an electronic survey via the social networking site Facebook, we carried out as a scientific research team, which naturally aimed to know how to receive and watch women staying at home in the governance of Constantine for the TV advertising. The effects that it leaves This kind of advertising on the values and behaviors and consolidation of the consumption pattern that serves the interest of advertisers and not the public’s interest especially if this audience is a crowd of women who are home-based and who, of course, have ample time and are totally free to watch a TV.
The role of using the television advertisements by the Algerian women staying at home in order to achieve their daily satisfactions -An electronic survey directed to a sample of women in the governance of Constantine, who use the social networking site facebook-
مقال
Keywords: امرأة ماكثة بالمنزل ، إعلان تلفزي، إشباع حاجات، التعرض، المشاهدة.; women staying at home, TV advertising, satisfying needs, exposure, viewing.